Automatic Telugu Summarizer - A.Pandian; Kumar, T.Vinay; Ram, G. Sai (International Journal of Psychosocial Rehabilitation, 2020)
The exponential development of online material data began with the clear demand for a persuasive and helpful plus that provides the simplest substance in an excessively fragmented sense, while saving center informatio. In this article, we are inclined to suggest an old, related extractive telugu single recording technique aimed at providing an adequate knowledge core. The predicted extractive methodology tests each sentence hooked through a mixture of observable and textual highlights in which a single description is used taking into consideration the meaning of the phrase, its inclusion and close range. Even, as a score-based and directed AI, run-down and ward encourage the use of the scheduled highlights were popular. We aim to find out the adequacy of the expected methodology across various analyzes under EASC corpus using live ROUGE. Contrasting with other existing associated research, the assessment of the trial demonstrates the consistency of the planned methodology as a way as measures of reality, analysis and F-score execution.